The Relationship between the Future Anxiety and Psychological Resilience of Adolosence: The Mediating Role of Life Satisfaction - Asiye Dursun; Murat Sinan Ozkan (Yaşam Becerileri Psikoloji Dergisi, 2019)
In this study, the effect of mediating role of life satisfaction in high school students' relationship between future anxiety and psychological resilience is investigated. Also, it is aimed to investigate whether the variables differ according to gender. The study included 278 female (68.5%) and 178 male (31.5%) high school students. In this study, Academic and Occupational Future Anxiety Scale, Child and Youth Resilience Measure, Life Satisfaction Scale and Personal Information Form were used. In this analysis using relational screening model, the mediator role analysis of Baron and Kenny was performed to determine the mediator effect of life satisfaction with t-test. In the study, it is observed that life satisfaction has a partial mediator role in the relationship between future anxiety and psychological resilience It is not seen that life satisfaction significantly differentiated according to gender variable in favor of males but there is no significant difference in future anxiety and psychological resilience variables.